SWOT Analysis Of Marketing Strategy On Elzatta - Firma Donna; Hamidah Tussifah (Islamic Business and Management Journal, 2020)
The Muslim population in the world is increasing every year according to the Pew Research Center's Forum on Religion & Public Life. Indonesia declared a world Muslim fashion center in 2020. Elzatta is a hijab brand with the tagline "Pesona Hijab Indonesia". In facing Indonesia as the center of world Muslim fashion in 2020, Elzatta needs to determine the company's position based on the SWOT matrix so that it can find out the appropriate strategy for the company. The purpose of this study was to determine Elzatta SWOT analysis of internal factors and external factors. This type of research is qualitative research with descriptive analysis method. Data retrieval is used by using observation, interview, and documentation techniques. The results obtained from the SWOT matrix analysis show that Elzatta's position is currently in quadrant I, namely growth strategy. These results are determined based on the average score on IFAS and EFAS so that the best alternative strategy SWOT matrix is obtained for business development, especially Elzatta marketing strategy with SO strategy, which is to maintain and improve product quality so that it can become a product of Indonesian pride.